2011
DOI: 10.1007/s13187-011-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in Attitudes Across Cancer Screenings in Medically Underserved Minority Populations

Abstract: While a wide range of behavioral and psychosocial literature explores attitudes and beliefs towards cancer screenings, fewer studies examine attitudes across cancer screening types. We draw on quantitative and qualitative findings from a 4-year prospective study based at a community health center serving diverse, low-income patients. Methods included self-report surveys (n=297), medical chart abstraction, and several qualitative methods with a subsample of participants. Participants included white, African–Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The literature has shown the strong influence of social networks on Vietnamese patients’ decision to be screened for CRC [41, 36]. Our study is consistent with Walsh et al’s findings that those who knew someone with CRC were more likely to be screened [50].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The literature has shown the strong influence of social networks on Vietnamese patients’ decision to be screened for CRC [41, 36]. Our study is consistent with Walsh et al’s findings that those who knew someone with CRC were more likely to be screened [50].…”
Section: Discussionsupporting
confidence: 91%
“…Two prior qualitative studies, using focus groups and in-depth interviews, respectively, suggest that social networks may be more influential than physician recommendation [41, 21], as participants were unable to remember what they talked about with their physician. However, that was not found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that a positive attitude toward one type of cancer screening is associated with positive attitudes toward others as well. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Surveys have been conducted in the past to understand knowledge and attitudes regarding prostate cancer and screening among men from various ethnicities. Shaw, Vivian, Orzech, Torres, and Armin (2012) (Squiers et al, 2013). Factors that were positively correlated with having a PSA test done were higher income, having had a PSA in the past two years, identifying as Black, and being somewhat to very worried concerning risk for prostate cancer diagnosis.…”
Section: Quantitative: Surveymentioning
confidence: 99%